1992
DOI: 10.1254/jjp.60.275
|View full text |Cite
|
Sign up to set email alerts
|

Possible Mechanisms of Action of the Antispasmodic Agent Tiropramide in the Isolated Detrusor from Rats.

Abstract: ABSTRACT-The effects of tiropramide hydrochloride on Ca 2+ induced contraction, cytoplasmic free Ca 2+ levels and tissue cyclic AMP concentrations were investigated to elucidate the mechanisms of its antispasmodic action in the isolated detrusor from rats. Tiropramide inhibited the Ca 2+ (3 mM) induced contractions of the isolated urinary bladder depolarized in a Ca2+free medium, and the IC50 value was 3.3 X 10-6 M. When tiropramide was added during the sustained phase of the K+ (60 mM) contracture, IC50 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…Tiropramide ((±)α-(benzoylamino)-4- [2-(diethylamino) ethoxy]-N,N-dipropyl-benzenepropanamide hydrochloride, CAS 55837-29-1) (see structure formula) has been known as a potent antispasmodic agent, and has been widely used for treatment of patients with disorders of the motility of the gastrointestinal, biliary and urinary tracts [1][2][3][4][5]. Its pharmacological effects have been reported to be potent on contractions provoked by chemical stimuli and less potent on vascular smooth muscle [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tiropramide ((±)α-(benzoylamino)-4- [2-(diethylamino) ethoxy]-N,N-dipropyl-benzenepropanamide hydrochloride, CAS 55837-29-1) (see structure formula) has been known as a potent antispasmodic agent, and has been widely used for treatment of patients with disorders of the motility of the gastrointestinal, biliary and urinary tracts [1][2][3][4][5]. Its pharmacological effects have been reported to be potent on contractions provoked by chemical stimuli and less potent on vascular smooth muscle [5].…”
Section: Introductionmentioning
confidence: 99%
“…In an animal study using the isolated smooth muscle, tiropramide inhibited Ca 2+ influx for the most part and, to a lesser extent, increased the intracellular cyclic adenosine monophosphate (cAMP) levels 9. This study using rabbit also found that tiropamide increased Ca 2+ absorption into microvesicles and decreased the amount of Ca 2+ released to stimulate the contraction of the smooth muscle by increasing cAMP; as a consequence the smooth muscle relaxed 9. In terms of the distribution of tiropramide, a study showed that the radioactivity of tiropramide lasted longer in the colon than in other organs after intravenous or oral administration,17 indicating relative colonic selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…One of the antispasmodics, tiropramide, is a derivative of tyrosine, and exerts a spasmolytic effect on the intestine through reducing Ca 2+ release into intestinal smooth muscle, rather than acting on the enteric nervous system 8,9. In a double-blind, placebo-controlled, randomized trial, tiropamide led to symptom improvement in terms of total symptom scores for 4 weeks, compared with 3 weeks in the placebo group; in addition, at week 4 abdominal pain was only improved in the tiropramide group 10.…”
Section: Introductionmentioning
confidence: 99%
“…Tiropramide exerts an antispasmodic effect on the intestine through reducing Ca 2+ release into the intestinal smooth muscle [61,62]. In a phase 4, double blind, randomized controlled trial of 245 patients, the mean change of visual analog scores for abdominal pain with tiropramide (100 mg thrice a day) was non-inferior to octylonium (20 mg thrice a day) [63].…”
Section: Tiropramidementioning
confidence: 99%